Somatic embryogenesis and plant regeneration from radicles of olive (Olea europaea ‘Chemlal’) zygotic embryos - Khayreddine TITOUH; Khadidja HADJ-MOUSSA; Nazim BOUFIS; Lakhdar KHELIFI (Acta Agriculturae Slovenica)
Olive improvement by biotechnological tools such as genetic transformation requires an efficient in vitro regeneration system. Somatic embryogenesis seems the most suitable process. Our work describes for the first time the regeneration of whole plants in the main olive cultivar in Algeria ‘Chemlal’ via somatic embryogenesis induced from radicles of mature zygotic embryos. The obtained results showed that the establishment of a competent embryogenic culture is highly influenced by the chemical composition of the calli induction and maintenance media as well as addition of growth regulators. More than 10 and 13 % of nodular calli were obtained after callogenesis respectively on MS and OMc solid media containing IBA and zeatin followed by transfer to the same media without zeatin and a reduced concentration of auxin, while embryogenesis rates of 3.3 and 6.7 % were obtained respectively with IAA on MS medium and NAA on both tested media. However, no embryogenesis was observed with 2, 4-D or control which induced less callogenesis. Subsequently, an ECO medium with IBA, zeatin and BA particularly in liquid culture, allows better calli proliferation and embryogenic expression compared to OM and MS media. Finally, matured somatic embryos germinate quickly on a solid OM basal medium and generate normal well-developed plantlets easily acclimatized to natural conditions.